Simulating knowledge: Saturation in ludonarrative fictional worlds - Navarrete Cardero, Luis; Vargas-Iglesias, Juan José (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article intends to apply the fictional worlds theory to the understanding of the structural conditions of revealed and not revealed worlds in videogames. In order to do so, we will work with to intensional saturation indexes, or degrees of knowledge and comprehension of the universe reachable by an ideal player, as seen in the six games chosen as objects of analysis. These indexes, based on the texture types offered by each example, determine the ways in which the different combinations articulate the heuristic scope of the player in the epistemic and deontic modalities. By means of it, this article intends to find a structural perspective of the narrative's nature of interactive world simulations, establishing basis from which to outline the assessments of the particular intensities.
Keywords: fictional worlds theory, videogames, Doležel, Genette, narrative modalities